2017
DOI: 10.1186/s12245-017-0156-5
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of emergency weight estimation systems in children—a systematic review and meta-analysis

Abstract: The safe and effective administration of fluids and medications during the management of medical emergencies in children depends on an appropriately determined dose, based on body weight. Weight can often not be measured in these circumstances and a convenient, quick and accurate method of weight estimation is required. Most methods in current use are not accurate enough, but the newer length-based, habitus-modified (two-dimensional) systems have shown significantly higher accuracy. This meta-analysis evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
113
3
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(123 citation statements)
references
References 153 publications
(199 reference statements)
5
113
3
2
Order By: Relevance
“…It has performed better than the Broselow tape in multiple previous studies. 2,4,7 The PAWPER tape did not perform as well in a recent study in a very obese population, however, and failed to achieve the same accuracy as in studies in the rest of the world. 7 As a result, the PAWPER XL tape was developed, which has 7 habitus scores instead of 5 and the length of the tape was extended from 153 cm to 180 cm.…”
Section: Introductionmentioning
confidence: 76%
“…It has performed better than the Broselow tape in multiple previous studies. 2,4,7 The PAWPER tape did not perform as well in a recent study in a very obese population, however, and failed to achieve the same accuracy as in studies in the rest of the world. 7 As a result, the PAWPER XL tape was developed, which has 7 habitus scores instead of 5 and the length of the tape was extended from 153 cm to 180 cm.…”
Section: Introductionmentioning
confidence: 76%
“…Para asegurar una buena estimación del peso, las ecuaciones deben cumplir idealmente cuatro características 24,25 : ser validadas en muestras de sujetos pediátricos que sean representativos de la población general, de fácil aplicación y rápida obtención, sin requerir métodos de cálculo avanzado con fácil recordación que permita su reproducibilidad, ser lo más cercanas al peso medido para asegurar la exactitud y precisión, estar disponibles para ser usadas en escenarios extra hospitalarios. Si bien el peso de un paciente es una característica que depende de múltiples variables, la estimación basada en la edad es una forma sencilla y útil de utilizar en escenarios especiales como la atención de urgencias o emergencias, atención pre hospitalaria, sistemas de atención ambulatoria (domiciliaria) o en la vía pública así como regiones apartadas 26 .…”
Section: Discussionunclassified
“…We were interested to learn about the PAWPER tape, as it quickly estimates TBW as well as IBW. The authors have demonstrated that an assessment of body habitus significantly improves the accuracy of tape-based systems, 2,3 which are more accurate than age-based formulas alone. 4 We are also very impressed with the development of the PAWPER XL-MAC system, which makes the assessment of body habitus objective by also measuring mid-arm circumference.…”
Section: Responsementioning
confidence: 99%
“…We agree that in patients who are obese, using IBW instead of TBW to calculate tidal volume is correct because lung size does not increase linearly with increasing body habitus. 1,2 The authors' proposed scaling for calculating tidal volume is very similar to how hydrophilic medications should be dosed in children who are of average weight and those who are obese.…”
mentioning
confidence: 99%